Pengaruh Komitmen Organisasi, Gaya Kepemimpinan Dan Komunikasi Kerja Terhadap Kinerja Karyawan PT Widatra Bhakti Departemen Supply Chain Bagian Gudang - Mufarrichah, Abidah; Asiyah, Siti; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this research is to find out and analyze the influence of organizational commitment, leadership style, work communication on the performance of PT Widatra Bhakti employees in the warehouse supply chain department. Sampling was carried out on employees of PT Widatra Bhakti in the warehouse supply chain department using a saturated sampling technique where all members of the population were used as samples. This research method uses multiple linear regression analysis with SPSS analysis tools. This research shows that organizational commitment, leadership style, and work communication have a simultaneous effect on employee performance. The test was carried out using a partial test, all variables had a significant positive effect on the dependent variable. Keywords : Organizational Commitment, Leadership Style, Work Communication, Employee Performance